Poor Reading Culture of Students and Its Effect on Their Academic Performance of English in Secondary Schools of Kisinga Sub-County Kasese District Uganda. - Munduwabo, Salumu (Kabale University, 2024)
The general objective of the study was to assess the Poor Reading Culture of Students and its Effect on their Academic Performance in English in Secondary Schools of Kisinga Sub-County in Kasese district.